Switch Off "Parallel Circuit": Insight of New Strategy of Simultaneously Suppressing Canonical and Noncanonical Inflammation Activation in Endotoxemic Mice. Issue 6 (18th May 2020) - Yan, Lei; Liang, Jiaqi; Zhou, Yi; Huang, Jian; Zhang, Tianshu; Wang, Xiaohui; Yin, Hang
Abstract: Sepsis is a life‐threatening inflammatory disease with a high mortality rate and huge implicative costs. Lipopolysaccharide (LPS) from gram‐negative bacteria activates toll‐like receptor 4 (TLR4) and may trigger septic shock. However, potent TLR4 inhibitors TAK‐242 and Eritoran have been terminated in phase III clinical trials because of inadequate efficacy. Inspired by the recently discovered intracellular, noncanonical LPS receptors, it is considered that TLR4‐mediated canonical and caspase‐mediated noncanonical inflammation can be seen as a "parallel circuit" to induce sepsis and endotoxemia. Logically, it is proposed that the dual inhibition of caspase‐4/5/11 and TLR4 can be a potential novel strategy to develop new therapeutics for sepsis. To verify the strategy, two potential compounds are found: Luteolin and Diacerein with substantial antiinflammatory activity in vitro and in vivo. The results show that the survival rate of endotoxemic mice treated by these compounds is increased remarkably. LPS‐induced organ damage is also prevented. Moreover, these compounds result in physical and mental recovery for endotoxemic mice. Notably, Luteolin exhibits better antiinflammatory activity than TAK‐242 at comparable TLR4‐inhibitory levels. These findings indicate that simultaneous inhibition of TLR4 and caspase‐4/5/11 can be an anticipative strategy defeating sepsis and endotoxemia, which can be translated into significant medical and economic benefits. Abstract : Bacterial lipopolysaccharide activates TLR4 and may trigger sepsis. However, the sepsis drugs targeting TLR4 have failed so far. Here, the dual inhibition of caspase‐4/5/11 and TLR4 is proposed as a potential novel therapeutic strategy for sepsis. Two potential compounds are found with substantial antiinflammatory activity in vitro and in vivo. Accordingly, this strategy is anticipative to defeat sepsis.